Mackerel Identification by Morphological Analysis and DNA Barcoding - Walaiporn Thongpradub; Kaewalee Viboonkit; Patcharaporn Narkthewan (Springer Link (Chiba Institute of Technology), 2026)
Rastrelliger genus are caught in large quantities in Thailand and this has led to declines in the natural populations of the fish. Attempts have been made to improve stocks through breeding programs. However, better methods of identifying fish species are required to improve the selection of breeding stock. In this research, we aimed to identify species by combining the morphological method and DNA barcoding. The results of the morphometric analysis of thirty fish samples were that there were 16 R. brachysoma and 14 R. kanagurta. The ratios of forked length to operculum depth for R. brachysoma and R. kanagurta were in the ranges of 3.6-4.1 and 4.5-5.1, respectively. The intestines of R. brachysoma were very long, which was apparent in the ratio of intestine length to fork length being in the range of 3.4-5.7. In contrast, the intestines of R. kanagurta were shorter and were only 0.8-1.9 times longer than the fork. Subsequently, all samples were identified by DNA barcoding. For a conclusive identification, samples had to have >99% similarity to reference sequences in both the GenBank and BOLD systems. Moreover, a phylogenetic tree constructed based on the COI sequences distinguished the fish samples into 2 major clades: R. brachysoma and R. kanagurta, which correlated with the genetic classification. For twenty-two samples, there was correlation between the morphological and genetic species assignment, but for 8 samples the morphological and genetic assignments were inconsistent. Therefore, in order to achieve accurate species identification, a combined morphometric- genetic analysis is recommended.
Keywords: Identification and Quantification in Food; Fish Biology and Ecology Studies; Ichthyology and Marine Biology